Coexistence of mitochondrial 12S rRNA C1494T and CO1/tRNA(Ser(UCN)) G7444A mutations in two Han Chinese pedigrees with aminoglycoside-induced and non-syndromic hearing loss - Yuan, Huijun; Chen, Jing; Liu, Xin; Cheng, Jing; Wang, Xinjian; Yang, Li; Yang, Shuzhi; Cao, Juyang; Kang, Dongyang; Dai, Pu; Zhai, Suoqiang; Han, Dongyi; et al. (Biochemical and biophysical research communications, 2007)
Mutations in mitochondrial DNA are one of the important causes of hearing loss. We report here the clinical, genetic, and molecular characterization of two Han Chinese pedigrees with maternally transmitted aminoglycoside-induced and nonsyndromic bilateral hearing loss. Clinical evaluation revealed the wide range of severity, age-at-onset, and audiometric configuration of hearing impairment in matrilineal relatives in these families. The penetrances of hearing loss in these pedigrees were 20% and 18%, when aminoglycoside-induced deafness was included. When the effect of aminoglycosides was excluded, the penetrances of hearing loss in these seven pedigrees were 10% and 15%. Sequence analysis of the complete mitochondrial genomes in these pedigrees showed the presence of the deafness-associated 12S rRNA C1494T and CO1/tRNA(Ser(UCN)) G7444A mutations. Their distinct sets of mtDNA polymorphism belonged to Eastern Asian haplogroup C4a1, while other previously identified six Chinese mitochondrial genomes harboring the C1494T mutation belong to haplogroups D5a2, D, R, and F1, respectively. This suggested that the C1494T or G7444A mutation occurred sporadically and multiplied through evolution of the mitochondrial DNA (mtDNA). The absence of functionally significant mutations in tRNA and rRNAs or secondary LHON mutations in their mtDNA suggest that these mtDNA haplogroup-specific variants may not play an important role in the phenotypic expression of the 12S rRNA C1494T and CO1/tRNA(Ser(UCN)) G7444A mutations in those Chinese families. However, aminoglycosides and other nuclear modifier genes play a modifying role in the phenotypic manifestation of the C1494T mutation in these Chinese families.